Solar Cell
By integrating a translucent electrode and a metal oxynitride electron transport layer in perovskite solar cells, electron density is increased, leading to improved photoelectric conversion efficiency and open circuit voltage.
Patent Information
- Application Number
- JP2022505788
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-12
- Filing Date
- 2020-12-28
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-12-28
AI Technical Summary
Perovskite solar cells have high photoelectric conversion efficiency but require further improvements to enhance their performance.
Incorporating a translucent electrode and an electron transport layer made of metal oxynitride with high electron conductivity between the first electrode and the photoelectric conversion layer, which contains a perovskite compound, to increase electron density and improve open circuit voltage.
The solution results in perovskite solar cells with enhanced photoelectric conversion efficiency, achieving high current density and open circuit voltage.
Smart Images

Figure 0007617571000003 
Figure 0007617571000004 
Figure 0007617571000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to solar cells. [Background technology]
[0002] In recent years, perovskite solar cells have been researched and developed. In perovskite solar cells, perovskite compounds represented by the chemical formula ABX3 (where A is a monovalent cation, B is a divalent cation, and X is a halogen anion) are used as photoelectric conversion materials.
[0003] Non-Patent Document 1 and Patent Document 1 disclose the use of a perovskite compound represented by the chemical formula CH3NH3SnI3 (hereinafter referred to as "MASnI3") as a photoelectric conversion material for a perovskite solar cell. Non-Patent Document 1 and Patent Document 1 also disclose a perovskite compound represented by the chemical formula (NH2)2CHSnI3 (hereinafter referred to as "FASnI3"). Patent Document 1 also discloses perovskite compounds represented by the chemical formula CH3NH3PbI3 (hereinafter referred to as "MAPbI3") and the chemical formula (NH2)2CHPbI3 (hereinafter referred to as "FAPbI3"), in which the divalent cation is Pb, as photoelectric conversion materials. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-17252 A [Non-patent literature]
[0005] [Non-Patent Document 1] Shuyan Shao et. Al. "Highly Reproducible Sn-Based Hybrid Perovskite Solar Cells with 9% Efficiency", Advanced Energy Materials, 2018, Vol. 8, 1702019 [Non-Patent Document 2] Atsushi Kogo et al., "Nb2O5 Blocking Layer for High Open-circuit Voltage Perovskite Solar Cells", Chem. Lett., 2015, Vol. 44, 829 - 830 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present disclosure is to provide a perovskite solar cell having high photoelectric conversion efficiency. [Means for solving the problem]
[0007] The solar cell according to the present disclosure comprises: first electrode, second electrode, A photoelectric conversion layer provided between the first electrode and the second electrode; and an electron transport layer provided between the first electrode and the photoelectric conversion layer; Equipped with Where: At least one electrode selected from the group consisting of the first electrode and the second electrode has light-transmitting properties; the photoelectric conversion layer contains a perovskite compound composed of monovalent cations, divalent cations, and halogen anions; The electron transport layer contains a metal oxynitride having electronic conductivity. Effect of the Invention
[0008] The present disclosure provides perovskite solar cells with high photoelectric conversion efficiency. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 shows the simulation results when the electron densities of the electron transport layer are 1×108 cm−3, 1×1010 cm−3, 1×1012 cm−3, 1×1014 cm−3, 1×1016 cm−3, 1×1018 cm−3 and 1×1020 cm−3. [Diagram 2] FIG. 2 illustrates a cross-sectional view of a solar cell according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 shows a cross-sectional view of a solar cell according to a variation of an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Terminology> As used herein, the term "perovskite compound" refers to a perovskite crystal structure represented by the chemical formula ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and structures having crystals similar thereto.
[0011] The term "perovskite solar cell" as used in this specification means a solar cell that contains a perovskite compound as a photoelectric conversion material.
[0012] As used herein, the term "tin-based perovskite compound" means a perovskite compound that contains tin.
[0013] <Knowledge that formed the basis of this disclosure> The findings on which the present disclosure is based are as follows.
[0014] Perovskite compounds have a band gap of about 1.1 to 1.6 eV. Therefore, perovskite compounds are suitable as photoelectric conversion materials for solar cells. Perovskite solar cells have been reported to have high photoelectric conversion efficiency, and further improvement in photoelectric conversion efficiency is required.
[0015] To improve the photoelectric conversion efficiency, it is necessary to increase the electron density of the electron transport layer from the current level. Figure 1 is a graph showing the relationship between the voltage (horizontal axis) and the current density (vertical axis) of the solar cell for each electron density of the electron transport layer. The graph shows the results of calculations performed using device simulation (software name: SCAPS). Figure 1 shows the relationship between the electron density of the electron transport layer and the current density of the solar cell for 8 cm -3 , 1×10 10 cm -3 , 1×10 12 cm -3 , 1×10 14 cm -3 , 1×10 16 cm -3 , 1×10 18 cm -3 and 1 × 10 20 cm -3 The simulation results for the case where the electron density of the electron transport layer is 0.8 V are shown in Fig. 1. As is clear from Fig. 1, by increasing the electron density of the electron transport layer, the open circuit voltage increases. The higher the electron density of the electron transport layer, the greater the built-in potential applied to the perovskite layer, and the higher the open circuit voltage. Therefore, by increasing the electron density of the electron transport layer, it is expected that the open circuit voltage and photoelectric conversion efficiency of the perovskite solar cell will increase. High efficiency (for example, 27 mA / cm at a voltage of 0.8 volts) 2 In order to obtain a current density of 1×10 or more, the electron density in the electron transport layer must be 1×10 16 cm -3 The electron density of the electron transport layer made of oxide-based electron transport materials such as TiO2 and Nb2O5 has been reported to be 1×10 15 cm -3 Therefore, there is a need for new electron transport materials that have high electron density.
[0016] Oxynitrides have a higher electron density than oxides that have been used as electron transport materials in the past. In oxides that generally become n-type semiconductors, oxygen sites become vacant, and these defect species act as donors, resulting in electron transport properties. On the other hand, in oxynitrides, nitrogen sites tend to become vacant in the atmosphere, and the nitrogen sites are easily replaced by oxygen ions. These two types of donor defect species in oxynitrides are more likely to form than oxygen vacancies in oxides, and supply more electrons, so oxynitrides have a higher electron density than oxides.
[0017] Based on these findings, the present inventors provide a solar cell that contains a perovskite compound and has an electron transport layer with high electron density.
[0018] <Embodiments of the present disclosure> Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings.
[0019] Fig. 2 shows a cross-sectional view of a solar cell 100 according to this embodiment. As shown in Fig. 2, the solar cell 100 of this embodiment includes a first electrode 2, a second electrode 6, a photoelectric conversion layer 4 provided between the first electrode 2 and the second electrode 6, and an electron transport layer 3 provided between the first electrode 2 and the photoelectric conversion layer 4.
[0020] The first electrode 2 faces the second electrode 6 such that the electron transport layer 3 and the photoelectric conversion layer 4 are located between the first electrode 2 and the second electrode 6. At least one electrode selected from the group consisting of the first electrode 2 and the second electrode 6 has light-transmitting properties. In this specification, the phrase "the electrode has light-transmitting properties" means that 10% or more of light having a wavelength of 200 to 2000 nanometers passes through the electrode.
[0021] (Photoelectric conversion layer 4) The photoelectric conversion layer 4 contains a perovskite compound composed of monovalent cations, divalent cations, and halogen anions as a photoelectric conversion material. The photoelectric conversion material is a light absorbing material.
[0022] In this embodiment, the perovskite compound may be a compound represented by the chemical formula ABX3, where A is a monovalent cation, B is a divalent cation, and X is a halogen anion.
[0023] In accordance with the terminology commonly used for perovskite compounds, A, B, and X are also referred to herein as the A site, B site, and X site, respectively.
[0024] In this embodiment, the perovskite compound may have a perovskite-type crystal structure represented by the chemical formula ABX3. As an example, a monovalent cation is located at the A site, a divalent cation is located at the B site, and a halogen anion is located at the X site.
[0025] Each of the A sites, B sites and X sites may be occupied by multiple types of ions.
[0026] (A Site) The monovalent cation located at the A site is not limited. Examples of the monovalent cation A are organic cations or alkali metal cations. Examples of the organic cations are methylammonium cation (i.e., CH3NH3 + ), formamidinium cation (i.e., NH2CHNH2 + ), phenylethylammonium cation (i.e., C6H5C2H4NH3 + ), or guanidinium cation (i.e., CH6N3 + ). An example of an alkali metal cation is the cesium cation (i.e., Cs + ).
[0027] For high photoelectric conversion efficiency, it is desirable for the monovalent cation A to contain a formamidinium cation.
[0028] The monovalent cations located at the A site may be composed of two or more types of cations.
[0029] The A site may comprise primarily formamidinium cations. The phrase "the A site comprises primarily formamidinium cations" means that the molar ratio of formamidinium cations to the total molar amount of monovalent cations is highest.
[0030] The A site may be substantially composed of formamidinium cations. The phrase "the A site is substantially composed of formamidinium cations" means that the molar ratio of the number of moles of formamidinium cations to the total number of moles of monovalent cations is 90% or more, preferably 95% or more.
[0031] (B Site) The divalent cation located at the B site is not limited. An example of the divalent cation A is a metal cation. An example of the metal cation is a lead ion (Pb 2+ ), tin ion (Sn 2+ ), germanium ion (Ge 2+ ), zinc ion (Zn 2+ ), cadmium ion (Cd 2+ ), beryllium ion (Be 2+ ), magnesium ion (Mg 2+ ), calcium ion (Ca 2+ ), strontium ion (Sr 2+ ), barium ion (Ba 2+ ), titanium ion (Ti 2+ ), vanadium ion (V 2+ ), chromium ion (Cr 2+ ), manganese ion (Mn 2+ ), iron ion (Fe 2 +), cobalt ion (Co 2+ ), nickel ion (Ni 2+ ), copper ions (Cu 2+ ), palladium ion (Pd 2+ ), platinum ions (Pt 2+ ), Neodymium (Nd 2+ ), samarium ion (Sm 2+ ), europium ion (Er 2+ ), Dilprosium ion (Dy2+ ), thulium ion (Tm 2+ ), ytterbium ion (Yb 2+ ), or neptunium ion (Np 2+ ).
[0032] For high photoelectric conversion efficiency, the divalent cation is tin ion (Sn 2+ ) and lead ions (Pb 2+ It is preferable that the compound contains at least one selected from the group consisting of:
[0033] The divalent cation located at the B site may be composed of two or more types of cations.
[0034] The divalent cations located at the B site may be composed of two or more non-divalent metal cations and may be treated as divalent cations on average. For example, if monovalent and trivalent cations have equal probability of occupying the B site, then on average for the entire system, a divalent cation is located at the B site. An example of such a monovalent cation is the lithium ion (Li + ), sodium ion (Na + ), potassium ion (K + ), rubidium ion (Rb + ), Cesium ion (Cs + ), copper ions (Cu + ), silver ions (Ag + ), gold ions (Au + ), mercury ions (Hg + ), indium ion (In + ) or thallium ion (Tl + ) An example of a trivalent cation is the scandium ion (Sc 3+ ), yttrium ion (Y 3+ ), lanthanum ion (La 3+ ), cerium ion (Ce 3+ ), praseodymium ion (Pr 3+ ), neodymium ion (Nd 3+ ), promethium ion (Pm 3+ ), samarium ion (Sm 3+), europium ion (Er 3+ ), gadolinium ion (Gd 3+ ), terbium ion (Tb 3+ ), Dysprosium (Dy 3+ ), holmium ion (Ho 3+ ), erbium ion (Er 3+ ), thulium ion (Tm 3+ ), ytterbium ion (Yb 3+ ), lutetium ion (Lu 3+ ), titanium ion (Ti 3+ ), Vanadium In(V 3+ ), chromium ion (Cr 3+ ), manganese ion (Mn 3+ ), boron ion (B 3+ ), aluminum ion (Al 3+ ), manganese ion (Mn 3+ ), iron ion (Fe 3+ ), cobalt ion (Co 3+ ), nickel ion (Ni 3+ ), copper ions (Cu 3+ ), niobium ion (Nb 3+ ), molybdenum ion (Mo 3+ ), ruthenium ion (Ru 3+ ), rhodium ion (Rh 3+ ), palladium ion (Pd 3+ ), silver ions (Ag 3+ ), tantalum ion (Ta 3+ ), iridium ion (Ir 3+ ), gold ions (Au 3+ ) Gallium ion (Ga 3+ ), indium ion (In 3+ ), thallium ion (Tl 3+ ), phosphorus ion (P 3+ ), arsenic ion (As 3+ ), antimony ion (Sb 3+ ) or bismuth ion (Bi 3+ ).
[0035] (X Site) For high photoelectric conversion efficiency, it is desirable that the halogen anion located at the X site contains, for example, an iodide ion. The halogen anion located at the X site may be composed of two or more kinds of halogen ions.
[0036] The X site may mainly contain iodide ions. The phrase "X site mainly contains iodide ions" means that the ratio of the molar amount of iodide ions to the total molar amount of halogen anions is the highest. The X site may be substantially composed of iodide ions. The phrase "X site is substantially composed of iodide ions" means that the molar ratio of the number of moles of iodide ions to the total number of moles of halogen anions is 90% or more, preferably 95% or more.
[0037] The photoelectric conversion layer 4 may contain a material other than the photoelectric conversion material. For example, the photoelectric conversion layer 4 may further contain a quencher substance for reducing the defect density of the perovskite compound. The quencher substance is a fluorine compound such as tin fluoride. The molar ratio of the quencher substance to the photoelectric conversion material may be 5% or more and 20% or less.
[0038] The photoelectric conversion layer 4 may mainly contain a perovskite compound composed of monovalent cations, divalent cations, and halogen anions.
[0039] The sentence "photoelectric conversion layer 4 mainly contains a perovskite compound composed of monovalent cations, divalent cations, and halogen anions" means that photoelectric conversion layer 4 contains 70 mass % or more (preferably 80 mass % or more) of a perovskite compound composed of monovalent cations, divalent cations, and halogen anions.
[0040] The photoelectric conversion layer 4 may contain impurities. The photoelectric conversion layer 4 may further contain a compound other than the above-mentioned perovskite compound.
[0041] The photoelectric conversion layer 4 may have a thickness of 100 nanometers or more and 10 micrometers or less, and preferably a thickness of 100 nanometers or more and 1000 nanometers or less. The thickness of the photoelectric conversion layer 4 depends on the magnitude of its light absorption.
[0042] The photoelectric conversion layer 4 can be formed by using a solution coating method or the like.
[0043] (electron transport layer 3) The electron transport layer 3 contains a metal oxynitride having electronic conductivity as an electron transport material. The electron density of a metal oxynitride is higher than that of a metal oxide. Therefore, when a metal oxynitride having electronic conductivity is compared with a metal oxide having electronic conductivity, the metal oxynitride is superior in terms of electron transport properties. Here, the metal oxynitride having electronic conductivity is defined as a metal oxynitride having an electron density of 1×10 -7 S cm -1 It is preferable that the metal oxynitride contained in the electron transport layer 3 has an electrical conductivity of 1×10 -6 S cm -1 More preferably, the electrical conductivity is 1×10 -5 S cm -1 For example, the electrical conductivity of TiO2, SnO2, and Nb2O5, which have been reported as electron transport materials, is 0.01 S cm -1 , 0.01 S cm -1 , and 1 × 10 -5 S cm -1 On the other hand, the electrical conductivity of Ta2O5, which has not been reported as an electron transport material, is 1×10 -8 S cm -1 It is.
[0044] As demonstrated in Comparative Examples 3 and 4 described later, a solar cell having an electron transport layer 3 formed from a metal oxynitride (for example, tantalum oxynitride according to Comparative Example 4) produced by adding nitrogen to a metal oxide having poor electronic conductivity (for example, tantalum oxide according to Comparative Example 3) has a significantly low photoelectric conversion efficiency (for example, 0%). In other words, a solar cell having poor electronic conductivity (for example, an electrical conductivity of 1×10 -8 S cm -1 Metal oxynitrides obtained by adding nitrogen to metal oxides (described below) have poor electronic conductivity like metal oxides, and therefore solar cells having an electron transport layer formed from such metal oxynitrides do not function as solar cells.
[0045] Metal oxynitrides are produced by adding nitrogen to metal oxides having electronic conductivity. Metal oxynitrides produced in this manner have high electron density. Perovskite solar cells having an electron transport layer 3 containing an oxynitride having high electron density are expected to have high open circuit voltages and high photoelectric conversion efficiency. That is, the solar cell according to this embodiment can achieve high photoelectric conversion efficiency.
[0046] Examples of metal oxides having electronic conductivity are Nb2O5, SnO2, TiO2, ZnO, In2O3, WO3, Fe2O3, CeO2, SrTiO3, Zn2SnO4, or BaSnO3. Therefore, in the solar cell according to this embodiment, examples of metal oxynitrides contained in the electron transport layer 3 as an electron transport material are: (i) Niobium oxynitride, such as that produced by adding nitrogen to Nb2O5 (ii) Tin oxynitride, such as that produced by adding nitrogen to SnO2 (iii) titanium oxynitrides, such as those prepared by adding nitrogen to TiO2; (iv) zinc oxynitrides, such as those prepared by adding nitrogen to ZnO; (v) indium oxynitride, such as that prepared by adding nitrogen to In2O3; (vi) tungsten oxynitride, such as that prepared by adding nitrogen to WO; (vii) iron oxynitrides, such as those prepared by adding nitrogen to Fe2O3; (viii) Cesium oxynitride, such as that prepared by adding nitrogen to CeO2; (ix) Strontium titanate nitride, such as that prepared by adding nitrogen to SrTiO3; (x) zinc tin nitride, such as that prepared by adding nitrogen to Zn2SnO4, or (xi) Barium tin nitride, such as that prepared by adding nitrogen to BaSnO3 That is, the metal oxynitride contained in the electron transport layer may be at least one selected from the group consisting of niobium oxynitride, tin oxynitride, titanium oxynitride, zinc oxynitride, indium oxynitride, tungsten oxynitride, iron oxynitride, cesium oxynitride, strontium titanate nitride, tin zinc oxide, and barium tin oxide. For higher photoelectric conversion efficiency, the metal oxynitride contained in the electron transport layer may be at least one selected from the group consisting of niobium oxynitride and tin oxynitride.
[0047] The perovskite oxide ABO3 also has electronic conductivity. Examples of perovskite oxides having electronic conductivity are: (i) an oxide having a divalent cation located on the A site and a tetravalent cation located on the B site; (ii) an oxide having a trivalent cation located on the A site and a trivalent cation located on the B site; or (iii) oxides with tetravalent cations located on the A site and divalent cations located on the B site; An example of a perovskite oxide is SrTiO3.
[0048] The spinel oxide A2BO4 also has electronic conductive and electron transport properties. Examples of spinel oxides with electronic conductivity are: (i) an oxide with a divalent cation located on the A site and a tetravalent cation located on the B site; or (ii) Oxides with a trivalent cation on the A site and a divalent cation on the B site An example of a spinel oxide is Zn2SnO4.
[0049] Here, in the perovskite-type oxide and spinel-type oxide, the divalent cation is a lead ion (Pb 2+ ), tin ion (Sn 2+ ), germanium ion (Ge 2+ ), zinc ion (Zn 2+ ), cadmium ion (Cd 2+ ), beryllium ion (Be 2+ ), magnesium ion (Mg 2+ ), calcium ion (Ca 2+ ), strontium ion (Sr 2+ ), barium ion (Ba 2+ ), titanium ion (Ti 2+ ), vanadium ion (V 2+ ), chromium ion (Cr 2+ ), manganese ion (Mn 2+ ), iron ion (Fe 2+ ), cobalt ion (Co 2+ ), nickel ion (Ni 2+ ), copper ions (Cu 2+ ), palladium ion (Pd 2+ ), platinum ions (Pt 2+ ), Neodymium (Nd 2+ ), samarium ion (Sm 2+ ), europium ion (Er 2+ ), Dilprosium ion (Dy 2+ ), thulium ion (Tm 2+ ), ytterbium ion (Yb 2+ ), or neptunium ion (Np 2+ ).
[0050] In the above perovskite-type oxides and spinel-type oxides, the trivalent cation is a scandium ion (Sc 3+ ), yttrium ion (Y 3+ ), lanthanum ion (La3+ ), cerium ion (Ce 3+ ), praseodymium ion (Pr 3+ ), neodymium ion (Nd 3+ ), promethium ion (Pm 3+ ), samarium ion (Sm 3+ ), europium ion (Er 3+ ), gadolinium ion (Gd 3+ ), terbium ion (Tb 3+ ), Dysprosium (Dy 3+ ), holmium ion (Ho 3+ ), erbium ion (Er 3+ ), thulium ion (Tm 3+ ), ytterbium ion (Yb 3+ ), lutetium ion (Lu 3+ ), titanium ion (Ti 3+ ), Vanadium In(V 3+ ), chromium ion (Cr 3+ ), manganese ion (Mn 3+ ), boron ion (B 3+ ), aluminum ion (Al 3+ ), manganese ion (Mn 3+ ), iron ion (Fe 3+ ), cobalt ion (Co 3+ ), nickel ion (Ni 3+ ), copper ions (Cu 3+ ), niobium ion (Nb 3+ ), molybdenum ion (Mo 3+ ), ruthenium ion (Ru 3+ ), rhodium ion (Rh 3+ ), palladium ion (Pd 3+ ), silver ions (Ag 3+ ), tantalum ion (Ta 3+ ), iridium ion (Ir 3+ ), gold ions (Au 3+ ) Gallium ion (Ga 3+ ), indium ion (In 3+ ), thallium ion (Tl 3+ ), phosphorus ion (P 3+ ), arsenic ion (As 3+), antimony ion (Sb 3+ ), or bismuth ion (Bi 3+ ).
[0051] In the above perovskite-type oxides and spinel-type oxides, the tetravalent cation is a carbon ion (C 4+ ), silicon ion (Si 4+ ), sulfur ion (S 4+ ), titanium ion (Ti 4+ ), vanadium ion (V 4+ ), chromium ion (Cr 4+ ), manganese ion (Mn 4+ ), iron ion (Fe 4+ ), cobalt ion (Co 4+ ), nickel ion (Ni 4+ ), germanium ion (Ge 4+ ), selenium ion (Se 4+ ), zirconium ion (Zr 4+ ), niobium ion (Nb 4+ ), molybdenum ion (Mo 4+ ), technetium ion (Tc 4+ ), ruthenium ion (Ru 4+ ), rhodium ion (Rh 4+ ), palladium ion (Pd 4+ ), tin ion (Sn 4+ ), tellurium ion (Te 4+ ), hafnium ion (Hf 4+ ), tantalum ion (Ta 4+ ), tungsten ions (W 4+ ), rhenium ion (Re 4+ ), osmium ion (Os 4+ ), iridium ion (Ir 4+ ), platinum ions (Pt 4+ ), lead ion (Pb 4+ ), polonium ion (Po 4+ ), cerium ion (Ce 4+ ), praseodymium ion (Pr 4+ ), or terbium ion (Tb 4+ ).
[0052] For high photoelectric conversion efficiency, it is desirable for the electron transport layer 3 to have a thickness of 2 nanometers or more. When the thickness is 2 nanometers or more, the increase in hole density due to the quantum effect is suppressed, so that the hole blocking function is not lost and the photoelectric conversion efficiency is improved.
[0053] In order to improve the photoelectric conversion efficiency of the solar cell in view of the low resistance of the electron transport layer 3, it is desirable for the electron transport layer 3 to have a thickness of 500 nanometers or less.
[0054] The electron density of the electron transport layer 3 containing a metal oxynitride is 10 16 cm -3 Over 10 20 cm -3 The electron density of the electron transport layer 3 may be 10 20 cm -3 When the electron density of the electron transport layer 3 is 10 or less, the interface recombination between the excess electrons in the electron transport layer 3 and the holes in the photoelectric conversion layer is suppressed. Therefore, the photoelectric conversion efficiency is improved. 16 cm -3 When the content is equal to or greater than this, the electron transporting property of the electron transport layer 3 is improved, and therefore the photoelectric conversion efficiency is improved.
[0055] When the electron transport layer 3 contains niobium oxynitride, the ratio N / O of the amount of substance of N to the amount of substance of O in the niobium oxynitride contained in the electron transport layer 3 may be more than 0 and not more than 1, or may be 0.05 or more and 0.28 or less. The value of the ratio N / O can be measured by X-ray photoelectron spectroscopy (hereinafter referred to as the "XPS method"), energy dispersive X-ray analysis (hereinafter referred to as the "EDX method"), inductively coupled plasma optical emission spectroscopy (hereinafter referred to as the "ICP-OES method"), or Rutherford backscattering spectrometry (hereinafter referred to as the "RBS method").
[0056] When the electron transport layer 3 contains tin oxynitride, the ratio N / O of the amount of substance of N to the amount of substance of O in the tin oxynitride contained in the electron transport layer 3 may be more than 0 and not more than 0.66, or may be 0.05 or more and 0.15 or less. The value of the ratio N / O can be measured by an XPS method, an EDX method, an ICP-OES method, or an RBS method.
[0057] The electron transport layer 3 may mainly contain a metal oxynitride having electronic conductivity. The electron transport layer 3 may be substantially composed of a metal oxynitride having electronic conductivity. The electron transport layer 3 may be composed only of a metal oxynitride having electronic conductivity.
[0058] The phrase "the electron transport layer 3 mainly contains a metal oxynitride having electronic conductivity" means that the electron transport layer 3 contains 50 mol % or more (preferably 60 mol % or more) of a metal oxynitride having electronic conductivity.
[0059] The phrase "the electron transport layer 3 is substantially made of a metal oxynitride having electronic conductivity" means that the electron transport layer 3 contains 90 mol % or more (preferably 95 mol % or more) of a metal oxynitride having electronic conductivity.
[0060] The electron transport layer 3 may contain a compound other than a metal oxynitride as an electron transport material. The electron transport material other than a metal oxynitride may be a material known as an electron transport material for solar cells. Hereinafter, for the sake of distinction, the metal oxynitride is referred to as the first electron transport material, and the electron transport material other than the metal oxynitride is referred to as the second electron transport material.
[0061] The second electron transport material is described below.
[0062] The second electron transport material may be a semiconductor having a band gap of 3.0 eV or more. When the electron transport layer 3 contains a semiconductor having a band gap of 3.0 eV or more, visible light and infrared light pass through the electron transport layer 3 to reach the photoelectric conversion layer 4. Examples of semiconductors having a band gap of 3.0 eV or more are organic or inorganic n-type semiconductors.
[0063] Examples of organic n-type semiconductors are imide compounds, quinone compounds, fullerenes, or derivatives of fullerenes.
[0064] Examples of inorganic n-type semiconductors are metal oxides, metal nitrides, and perovskite oxides.
[0065] Examples of metal oxides are oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, or Cr. TiO2 is preferred.
[0066] An example of a metal nitride is GaN.
[0067] Examples of perovskite oxides are SrTiO3 or CaTiO3.
[0068] The electron transport layer 3 may be in contact with the photoelectric conversion layer 4. Alternatively, the electron transport layer 3 may not be in contact with the photoelectric conversion layer 4. When the electron transport layer 3 is in contact with the photoelectric conversion layer 4, the electron transport material containing an oxynitride may be provided on the surface of the electron transport layer 3 in contact with the photoelectric conversion layer 4.
[0069] The electron transport layer 3 may be composed of multiple layers formed of different electron transport materials. When the electron transport layer 3 is composed of multiple layers, the layer in contact with the photoelectric conversion layer 4 may contain a metal oxynitride having electronic conductivity.
[0070] 2, in the solar cell 100, a first electrode 2, an electron transport layer 3, a photoelectric conversion layer 4, a hole transport layer 5, and a second electrode 6 are laminated in this order on a substrate 1. That is, the hole transport layer 5 is provided between the second electrode 6 and the photoelectric conversion layer 4. The solar cell 100 may not have the substrate 1. The solar cell 100 may not have the hole transport layer 5.
[0071] Each component of the solar cell 100 will now be described in detail.
[0072] (Substrate 1) The substrate 1 holds the first electrode 2, the photoelectric conversion layer 4, and the second electrode 6. The substrate 1 may be formed of a transparent material. An example of the substrate 1 is a glass substrate or a plastic substrate. An example of the plastic substrate is a plastic film. If the first electrode 2 has sufficient strength, the solar cell 100 does not need to have the substrate 1 because the first electrode 2 holds the photoelectric conversion layer 4 and the second electrode 6.
[0073] (First electrode 2 and second electrode 6) The first electrode 2 and the second electrode 6 are conductive. At least one of the first electrode 2 and the second electrode 6 is translucent. Light in the visible to near infrared range can pass through the translucent electrode. The translucent electrode can be made of a transparent and conductive material.
[0074] Examples of such materials are: (i) titanium oxide doped with at least one element selected from the group consisting of lithium, magnesium, niobium, and fluorine; (ii) gallium oxide doped with at least one element selected from the group consisting of tin and silicon; (iii) gallium nitride doped with at least one element selected from the group consisting of silicon and oxygen; (iv) indium-tin oxide, (v) tin oxide doped with at least one element selected from the group consisting of antimony and fluorine; (vi) zinc oxide doped with at least one of boron, aluminum, gallium, and indium; or (vii) any combination thereof It is.
[0075] The light-transmitting electrode can be formed by providing a light-transmitting pattern using a non-transparent material. Examples of the light-transmitting pattern include a line-shaped, wavy-shaped, lattice-shaped, or punched metal pattern in which a large number of fine through-holes are regularly or irregularly arranged. When the light-transmitting electrode has these patterns, light can be transmitted through the portion where the electrode material is not present. Examples of the non-transparent material are platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, or an alloy containing any of these. A conductive carbon material may be used as the non-transparent material.
[0076] Since the solar cell 100 includes the electron transport layer 3 between the photoelectric conversion layer 4 and the first electrode 2, the first electrode 2 does not need to have a blocking property against holes from the photoelectric conversion layer 4. Therefore, the material of the first electrode 2 may be a material that can be in ohmic contact with the photoelectric conversion layer 4.
[0077] When the solar cell 100 does not include the hole transport layer 5, the second electrode 6 is formed of, for example, a material having blocking properties against electrons from the photoelectric conversion layer 4. In this case, the second electrode 6 does not make ohmic contact with the photoelectric conversion layer 4. The blocking properties against electrons from the photoelectric conversion layer 4 refer to a property that allows only holes generated in the photoelectric conversion layer 4 to pass and does not allow electrons to pass. The Fermi energy of the material having blocking properties against electrons is lower than the energy level of the lower end of the conduction band of the photoelectric conversion layer 4. The Fermi energy of the material having blocking properties against electrons may be lower than the Fermi energy level of the photoelectric conversion layer 4. Examples of materials having blocking properties against electrons are platinum, gold, or carbon materials such as graphene.
[0078] When the solar cell 100 has a hole transport layer 5 between the photoelectric conversion layer 4 and the second electrode 6, the second electrode 6 does not need to have a blocking property against electrons from the photoelectric conversion layer 4. In this case, the second electrode 6 may be in ohmic contact with the photoelectric conversion layer 4.
[0079] A material that blocks holes from the photoelectric conversion layer 4 may not be light-transmitting. A material that blocks electrons from the photoelectric conversion layer 4 may also not be light-transmitting. Therefore, when the first electrode 2 or the second electrode 6 is formed using these materials, the first electrode 2 or the second electrode 6 has the above-mentioned pattern that allows light to pass through the first electrode 2 or the second electrode 6.
[0080] The light transmittance of each of the first electrode 2 and the second electrode 6 may be 50% or more, or may be 80% or more. The wavelength of light that transmits through the electrode depends on the absorption wavelength of the photoelectric conversion layer 4. The thickness of each of the first electrode 2 and the second electrode 6 is, for example, in the range of 1 nanometer or more and 1000 nanometers or less.
[0081] (Hole transport layer 5) The hole transport layer 5 is composed of an organic material or an inorganic semiconductor. Representative examples of organic materials used as the hole transport layer 5 include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene (hereinafter referred to as "spiro-OMeTAD"), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as "PTAA"), poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as "P3HT"), poly(3,4-ethylenedioxythiophene) (hereinafter referred to as "PEDOT"), or copper phthalocyanine (hereinafter referred to as "CuPC").
[0082] Examples of inorganic semiconductors are Cu2O, CuGaO2, CuSCN, CuI, and NiO. x , MoO x , V2O5, or carbon materials such as graphene oxide.
[0083] The hole transport layer 5 may include a plurality of layers formed from different materials.
[0084] The thickness of the hole transport layer 5 may be 1 nanometer or more and 1000 nanometers or less, 10 nanometers or more and 500 nanometers or less, or 10 nanometers or more and 50 nanometers or less. If the thickness of the hole transport layer 5 is 1 nanometer or more and 1000 nanometers or less, sufficient hole transport properties can be exhibited. Furthermore, if the thickness of the hole transport layer 5 is 1 nanometer or more and 1000 nanometers or less, the resistance of the hole transport layer 5 is low, so that light is converted to electricity with high efficiency.
[0085] The hole transport layer 5 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent stabilize the holes in the hole transport layer 5.
[0086] Examples of the supporting electrolyte are ammonium salts or alkali metal salts. Examples of the ammonium salts are tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts, or pyridinium salts. Examples of the alkali metal salts are lithium bis(trifluoromethanesulfonyl)imide (hereinafter referred to as "LiTFSI"), LiPF6, LiBF4, lithium perchlorate, or potassium tetrafluoroborate.
[0087] The solvent contained in the hole transport layer 5 may have high ionic conductivity. The solvent may be an aqueous solvent or an organic solvent. From the viewpoint of stabilizing the solute, an organic solvent is preferable. Examples of organic solvents are heterocyclic compounds such as tert-butylpyridine, pyridine, or n-methylpyrrolidone.
[0088] The solvent contained in the hole transport layer 5 may be an ionic liquid. The ionic liquid may be used alone or in a mixture with other solvents. Ionic liquids are desirable in terms of low volatility and high flame retardancy.
[0089] Examples of ionic liquids are imidazolium compounds such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine compounds, cycloaliphatic amine compounds, aliphatic amine compounds, or azonium amine compounds.
[0090] (Effects of solar cells) Next, the basic effects of the solar cell 100 will be described. When the solar cell 100 is irradiated with light, the photoelectric conversion layer 4 absorbs the light, and excited electrons and holes are generated inside the photoelectric conversion layer 4. The excited electrons move to the electron transport layer 3. Meanwhile, the holes generated in the photoelectric conversion layer 4 move to the hole transport layer 5. The electron transport layer 3 is connected to the first electrode 2, and the hole transport layer 5 is connected to the second electrode 6, so that a current is taken out from the first electrode 2 functioning as a negative electrode and the second electrode 6 functioning as a positive electrode.
[0091] (100% solar cell manufacturing method) The solar cell 100 can be produced, for example, by the following method.
[0092] First, the first electrode 2 is formed on the surface of the substrate 1 by chemical vapor deposition (hereinafter referred to as "CVD") or sputtering.
[0093] Next, the electron transport layer 3 is formed on the first electrode 2 by, for example, a sputtering method.
[0094] For example, a metal oxide having electron conductivity is used as a target for use in the sputtering method. Using such a target made of a metal oxide, a film containing a metal oxynitride is formed by sputtering in an atmosphere containing nitrogen gas. The formed film containing a metal oxynitride is the electron transport layer 3.
[0095] The photoelectric conversion layer 4 is formed on the electron transport layer 3. The photoelectric conversion layer 4 can be formed, for example, as follows. As an example, (HC(NH2)2) 1-y-z (C6H5CH2CH2NH3)y(CH6N3) zSnI3 (where 0 < y, 0 < z, and 0 < (y + z) < 1, hereinafter referred to as "FA 1-y-z PEA y GA z SnI3"), a method for forming a photoelectric conversion layer 4 containing a perovskite compound is described.
[0096] First, SnI2, HC(NH2)2I (hereinafter referred to as "FAI"), C6H5CH2CH2NH3I (hereinafter referred to as "PEAI"), and CH6N3I (hereinafter referred to as "GAI") are added to an organic solvent to obtain a mixed solution. Examples of the organic solvent are a mixture of dimethyl sulfoxide (hereinafter referred to as "DMSO") and N,N-dimethylformamide (hereinafter referred to as "DMF") (DMS:DMF = 1:1 (volume ratio)).
[0097] The molar concentration of SnI2 may be 0.8 mol / L or more and 2.0 mol / L or less, and may also be 0.8 mol / L or more and 1.5 mol / L or less.
[0098] The molar concentration of FAI may be 0.8 mol / L or more and 2.0 mol / L or less, and may also be 0.8 mol / L or more and 1.5 mol / L or less.
[0099] The molar concentration of PEAI may be 0.1 mol / L or more and 0.6 mol / L or less, and may also be 0.3 mol / L or more and 0.5 mol / L or less.
[0100] The molar concentration of GAI may be 0.1 mol / L or more and 0.6 mol / L or less, and may also be 0.3 mol / L or more and 0.5 mol / L or less.
[0101] Next, the mixed solution is heated to a temperature of 40°C or more and 180°C or less. In this way, a mixed solution in which SnI2, FAI, PEAI, and GAI are dissolved is obtained. Subsequently, the mixed solution is left at room temperature.
[0102] Next, the mixed solution is applied onto the electron transport layer 3 by spin coating to form a coating film. The coating film is then heated at a temperature of 40° C. to 100° C. for 15 minutes to 1 hour. This forms the photoelectric conversion layer 4. When the mixed solution is applied by spin coating, a poor solvent may be dropped during spin coating. Examples of the poor solvent include toluene, chlorobenzene, or diethyl ether.
[0103] The mixed solution may contain a quencher substance such as tin fluoride. The concentration of the quencher substance may be 0.05 mol / L or more and 0.4 mol / L or less. The quencher substance suppresses the generation of defects in the photoelectric conversion layer 4. The cause of the generation of defects in the photoelectric conversion layer 4 is, for example, Sn 4+ The increase in the amount of Sn vacancies is due to the increase in the amount of Sn.
[0104] A hole transport layer 5 is formed on the photoelectric conversion layer 4. Examples of the method for forming the hole transport layer 5 include a coating method or a printing method. Examples of the coating method include a doctor blade method, a bar coating method, a spray method, a dip coating method, or a spin coating method. An example of the printing method is a screen printing method. A hole transport layer 5 may be obtained by mixing a plurality of materials, and then the hole transport layer 5 may be pressed or baked. When the material of the hole transport layer 5 is an organic low molecular weight substance or an inorganic semiconductor, the hole transport layer 5 may be prepared by a vacuum deposition method.
[0105] Finally, the second electrode 6 is formed on the hole transport layer 5. In this manner, the solar cell 100 is obtained. The second electrode 6 can be formed by a CVD method or a sputtering method.
[0106] 3 shows a cross-sectional view of a modified example of the solar cell of the embodiment. Unlike the solar cell 100 shown in FIG.
[0107] In the solar cell 200 shown in FIG. 3, a first electrode 2, a porous layer 7, an electron transport layer 3, a photoelectric conversion layer 4, a hole transport layer 5, and a second electrode 6 are laminated in this order on a substrate 1. The porous layer 7 includes a porous body. The porous body includes pores. The solar cell 200 may not have the substrate 1. The solar cell 200 may not have the hole transport layer 5.
[0108] The pores in the porous layer 7 are connected from the portion in contact with the first electrode 2 to the portion in contact with the electron transport layer 3. The pores in the porous layer 7 are filled with the material of the electron transport layer 3. Since the first electrode 2 is in contact with the electron transport layer 3, electrons move directly from the electron transport layer 3 to the first electrode 2.
[0109] Next, the basic effects of the solar cell 200 will be described. When the solar cell 200 is irradiated with light, the photoelectric conversion layer 4 absorbs the light and generates excited electrons and holes. The excited electrons move to the electron transport layer 3. Meanwhile, the holes generated in the photoelectric conversion layer 4 move to the hole transport layer 5. As described above, the electron transport layer 3 and the hole transport layer 5 are electrically connected to the first electrode 2 and the second electrode 6, respectively, so that a current is taken out from the first electrode 2 and the second electrode 6, which function as a negative electrode and a positive electrode, respectively.
[0110] The porous layer 7 facilitates the formation of the photoelectric conversion layer 4. The electron transport layer 3 formed on the porous layer 7 can cover the surface and pore walls of the porous layer 7. Since the thickness of the electron transport layer 3 is small, the surface and pore shapes of the porous layer 7 are maintained. In this case, the material of the photoelectric conversion layer 4 also penetrates into the inside of the pores of the porous layer 7 covered with the electron transport layer 3. Therefore, the possibility that the material of the photoelectric conversion layer 4 is repelled or aggregated on the surface of the electron transport layer 3 is reduced. Therefore, the porous layer 7 serves as a scaffold for the photoelectric conversion layer 4, and the photoelectric conversion layer 4 can be formed as a uniform film. The photoelectric conversion layer 4 can be formed by applying a solution to the electron transport layer 3 by spin coating and heating it.
[0111] Light scattering occurs due to the porous layer 7. This can increase the optical path length of light passing through the photoelectric conversion layer 4. The increase in the optical path length can increase the amount of electrons and holes generated in the photoelectric conversion layer 4.
[0112] The solar cell 200 can be produced by the same method as the solar cell 100. The porous layer 7 is formed on the first electrode 2 by, for example, a coating method.
[0113] (Porous layer 7) The porous layer 7 serves as a base for forming the photoelectric conversion layer 4. The porous layer 7 does not impede the movement of electrons from the photoelectric conversion layer 4 to the first electrode 2.
[0114] The porous layer 7 includes a porous body. An example of the porous body is a porous body in which insulating or semiconducting particles are connected. An example of the insulating particles is aluminum oxide or silicon oxide. An example of the semiconducting particles is inorganic semiconductor particles. An example of the inorganic semiconductor is a metal oxide (including perovskite oxide), a metal sulfide, or a metal chalcogenide. An example of the metal oxide is an oxide of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, or Cr. TiO2 is preferable. An example of the perovskite oxide is SrTiO3 or CaTiO3. An example of the metal sulfide is CdS, ZnS, In2S3, SnS, PbS, Mo2S, WS2, Sb2S3, Bi2S3, ZnCdS2, or Cu2S. Examples of metal chalcogenides are CdSe, CsSe, In2Se3, WSe2, HgS, SnSe, PbSe, or CdTe.
[0115] The thickness of the porous layer 7 may be 0.01 micrometers or more and 10 micrometers or less, or 0.1 micrometers or more and 1 micrometer or less. The surface roughness of the porous layer 7 may be large. Specifically, the surface roughness coefficient given by effective area / projected area may be 10 or more, or may be 100 or more. The projected area is the area of a shadow that is cast behind an object when light is shone on the object from the front. The effective area is the actual surface area of the object. The effective area can be calculated from the volume calculated from the projected area and thickness of the object, and the specific surface area and bulk density of the material that constitutes the object. The specific surface area is measured, for example, by a nitrogen adsorption method.
[0116] (Example) Hereinafter, the present disclosure will be described in more detail with reference to examples. As described below, in Examples 1 to 5 and Comparative Examples 1 to 4, solar cells having an electron transport layer and a photoelectric conversion layer containing a perovskite compound were fabricated. Furthermore, the characteristics of each solar cell were evaluated. Each solar cell according to Examples 1 to 5 and Comparative Examples 1 to 4 was a perovskite solar cell having the same structure as the perovskite solar cell 100 shown in FIG. 2.
[0117] [Example 1] A glass substrate (manufactured by Nippon Sheet Glass) having an indium-doped SnO2 layer on its surface was prepared. The glass substrate and the SnO2 layer served as the substrate 1 and the first electrode 2, respectively. The glass substrate had a thickness of 1 millimeter.
[0118] Niobium oxide (manufactured by Toshima Manufacturing Co., Ltd.) represented by the chemical formula Nb2O5 was used as the target. A film was formed on the SnO2 layer of the above glass substrate by sputtering at room temperature. Nitrogen gas (flow rate: 1 sccm), oxygen gas (flow rate: 0.1 sccm), and argon gas (flow rate: 10 sccm) were supplied to the chamber. The pressure in the chamber during sputtering was 0.5 Pa. The RF power supplied to the target was 100 W. The sputtering treatment of the target was carried out for one and a half minutes under the above conditions. In this way, an electron transport layer 3 composed of a niobium oxynitride film was formed. The electron transport layer 3 had a thickness of 8 nanometers. In this way, an evaluation sample was prepared. The prepared sample was transported from the air atmosphere to a nitrogen atmosphere.
[0119] A coating solution containing SnI2, SnF2 and FAI (all manufactured by Sigma-Aldrich) was prepared. The solvent of the coating solution was a mixed solvent of DMSO and DMF. The volume ratio of DMSO and DMF in the mixed solvent was 1:1. The concentration of SnI2 in the coating solution was 1.2 mol / L. The concentration of SnF2 in the coating solution was 1.2 mol / L. The concentration of FAI in the coating solution was 1.2 mol / L. Next, 80 microliters of the coating solution was applied onto the electron transport layer 3 by spin coating. In this way, a coating film was formed. The coating film was formed inside a glove box. The inside of the glove box was filled with N2. The thickness of the coating film was 500 nm. Next, the coating film was baked under the conditions of 120°C and 30 minutes. In this way, a photoelectric conversion layer 4 was formed. A hot plate was used for baking. The formed photoelectric conversion layer 4 mainly contained a tin-based perovskite compound of FASnI3.
[0120] Next, 80 microliters of a toluene solution containing PTAA (manufactured by Sigma-Aldrich) at a concentration of 10 mg / mL was applied by spin coating onto the photoelectric conversion layer 4, thus forming a hole transport layer 5. The formation of the hole transport layer 5 was carried out inside a glove box. The thickness of the hole transport layer 5 was confirmed by analyzing a cross section using a scanning electron microscope (hereinafter sometimes referred to as "SEM", Helios G3 manufactured by FEI).
[0121] Finally, a gold film having a thickness of 120 nm was deposited by vapor deposition on the hole transport layer 5. In this way, the second electrode 6 was formed. Then, in a nitrogen atmosphere, an ultraviolet curing resin (Nagase ChemteX Corporation, model number: model number XNR 5516Z-B1) was applied around the part where the second electrode 6 was formed, and nitrogen sealing was performed from above with glass. Then, the device was transported from the nitrogen atmosphere to the air atmosphere. Next, the ultraviolet curing resin was cured by irradiating ultraviolet rays for 15 minutes, and sealing was completed. In this way, the solar cell of Example 1 was obtained.
[0122] [Example 2] In Example 2, nitrogen gas (flow rate: 5 sccm), oxygen gas (flow rate: 0.1 sccm), and argon gas (flow rate: 10 sccm) were supplied to the chamber in forming the electron transport layer 3. Except for this, the solar cell of Example 2 was obtained in the same manner as in Example 1.
[0123] [Example 3] In Example 3, nitrogen gas (flow rate: 10 sccm), oxygen gas (flow rate: 0.1 sccm), and argon gas (flow rate: 5 sccm) were supplied to the chamber in forming the electron transport layer 3. Except for this, the solar cell of Example 3 was obtained in the same manner as in Example 1.
[0124] [Example 4] In Example 4, tin oxide (manufactured by Toshima Manufacturing Co., Ltd.) represented by the chemical formula SnO2 was used as a target in forming the electron transport layer 3, and nitrogen gas (flow rate: 10 sccm), oxygen gas (flow rate: 0.1 sccm), and argon gas (flow rate: 5 sccm) were supplied to the chamber. Except for these, the solar cell of Example 4 was obtained in the same manner as in Example 1.
[0125] [Example 5] In Example 5, tin oxide (manufactured by Toshima Manufacturing Co., Ltd.) represented by the chemical formula SnO2 was used as a target in forming the electron transport layer 3, and nitrogen gas (flow rate: 10 sccm), oxygen gas (flow rate: 0.1 sccm), and argon gas (flow rate: 1 sccm) were supplied to the chamber. Except for these, the solar cell of Example 5 was obtained in the same manner as in Example 1.
[0126] [Comparative Example 1] In Comparative Example 1, nitrogen gas was not supplied to the chamber during the formation of the electron transport layer 3. Except for this, the solar cell of Comparative Example 1 was obtained in the same manner as in Example 1.
[0127] [Comparative Example 2] In Comparative Example 2, tin oxide (manufactured by Toshima Manufacturing Co., Ltd.) represented by the chemical formula SnO2 was used as a target in forming the electron transport layer 3, and nitrogen gas was not supplied to the chamber. Except for these, the solar cell of Comparative Example 2 was obtained in the same manner as in Example 1.
[0128] [Comparative Example 3] In Comparative Example 3, tantalum oxide (manufactured by Toshima Manufacturing Co., Ltd.) represented by the chemical formula Ta2O5 was used as a target in forming the electron transport layer 3, and nitrogen gas was not supplied to the chamber. Except for these, the solar cell of Comparative Example 3 was obtained in the same manner as in Example 1.
[0129] [Comparative Example 4] In Comparative Example 4, tantalum oxide represented by the chemical formula Ta2O5 was used as a target in forming the electron transport layer 3, and nitrogen gas (flow rate: 5 sccm), oxygen gas (flow rate: 0.1 sccm), and argon gas (flow rate: 10 sccm) were supplied to the chamber. Except for these, the solar cell of Comparative Example 4 was obtained in the same manner as in Example 1.
[0130] [Composition Measurement] In each of the Examples and Comparative Examples, the composition of the electron transport material contained in the electron transport layer 3 included in the sample was identified using an XPS measurement device (manufactured by ULVAC-PHI, Inc., product name: PHI 5000 VersaProbe). AlKα rays were used as the X-ray source. The N / O ratio was determined by this measurement.
[0131] [Electron density measurement] In Examples 1 to 4 and Comparative Examples 1 to 3, the electron density of the electron transport layer 3 contained in the sample was calculated from the Fermi energy measured by the XPS method and the transmittance measurement method.
[0132] For the electron transport layer 3 included in each sample, the energy difference between the top of the valence band and the Fermi energy was obtained using an XPS measurement device (manufactured by ULVAC-PHI, Inc., product name: PHI 5000 VersaProbe).
[0133] The transmittance of the electron transport layer 3 included in each sample was measured using a transmittance measuring device (manufactured by Shimadzu Corporation, product name: SlidSpec-3700). Then, the band gap value of each electron transport layer 3 was obtained from the measured transmittance.
[0134] Based on the difference between the valence band top and the Fermi energy thus obtained, and the band gap value, the energy difference between the conduction band bottom and the Fermi energy of the electron transport layer 3 was calculated.
[0135] The difference between the conduction band edge and the Fermi energy (E C -EF ) was substituted into the following equation (1), and the electron density (n) was calculated.
number
[0136] [Calculation of electrical conductivity] The value of electron density n obtained by the above formula (1) is substituted into the following formula (2): In this way, the electrical conductivity σ was obtained. σ = qnμ(2) In the above formula (2), the value of q is the elementary charge. The value of μ is the carrier mobility. Here, the value of the carrier mobility μ is 0.291 cm 2 / Vs (that is, the value of the carrier mobility of the oxide film formed by the sputtering method) was used.
[0137] [Evaluation of photoelectric conversion efficiency] Each solar cell in the examples and comparative examples was subjected to a solar simulator (spectrometer: BPS X300BA) at 100 mW / cm 2 The solar cells were irradiated with artificial sunlight having an illuminance of 100 nm to measure the photoelectric conversion efficiency.
[0138] Table 1 shows the following in the examples and comparative examples. (i) In the preparation of the electron transport layer, the target material used, the presence or absence of nitrogen gas, and the materials contained in the prepared electron transport layer; (ii) a photoelectric conversion material contained in a photoelectric conversion layer; (iii) the ratio N / O in the electron transport layer; (iv) The energy difference between the conduction band edge and the Fermi energy in the electron transport layer, (v) the electron density in the electron transport layer; (vi) electrical conductivity in the electron transport layer, and (vii) Photoelectric conversion efficiency of solar cells Shows.
[0139] Comparing Examples 1 to 3 with Comparative Example 1, the electron transport layer containing niobium oxynitride has a higher electron density and a higher photoelectric conversion efficiency than the electron transport layer containing niobium oxide to which no nitrogen is added. Comparing Example 1 with Example 2, in the range of the ratio N / O of 0.05 to 0.28, the electron density increases and the photoelectric conversion efficiency improves as the nitrogen composition in the electron transport layer increases. Similarly, comparing Example 4 with Comparative Example 2, the electron transport layer containing tin oxynitride has a higher electron density and a higher photoelectric conversion efficiency than the electron transport layer containing tin oxide to which no nitrogen is added. Therefore, oxynitrides have a higher electron density than oxides. As a result, the electron transport layer containing oxynitrides can realize a solar cell with improved photoelectric conversion efficiency.
[0140] On the other hand, as is clear from a comparison between Example 1 and Comparative Example 4, when tantalum oxynitride is used as an electron transport material, the electron conductivity is poor. Therefore, the photoelectric conversion function is inhibited, and the solar cell does not function. This means that when an oxide such as tantalum oxide in Comparative Example 5, which has poor electronic conductivity and does not function as an electron transport layer, is used as a sputtering target, even if an oxynitride is produced by adding nitrogen, the electronic conductivity of the oxynitride is poor as with the oxide. Therefore, such an oxynitride does not function as an electron transport layer. In addition, considering the photoelectric conversion efficiency of Comparative Example 3 and Comparative Example 4, it is estimated that the electrical conductivity in the electron transport layer of Comparative Example 4 is about the same as that in the electron transport layer of Comparative Example 3. From the above, a solar cell with high photoelectric conversion efficiency can be realized by using an oxynitride obtained by adding nitrogen to an oxide having electron transport properties such as niobium oxide or tin oxide for the electron transport layer.
[0141] [Table 1] [Industrial Applicability]
[0142] The solar cell of the present disclosure is useful, for example, as a solar cell to be installed on a roof. [Explanation of symbols]
[0143] 1 Board 2 1st electrode 3 Electron transport layer 4 Photoelectric conversion layer 5. Hole transport layer 6 1st electrode 7 Porous layer 100, 200 Solar cells
Claims
1. A solar cell comprising: a first electrode; a second electrode, A photoelectric conversion layer provided between the first electrode and the second electrode; and an electron transport layer provided between the first electrode and the photoelectric conversion layer; Equipped with Where: At least one electrode selected from the group consisting of the first electrode and the second electrode has light-transmitting properties; the photoelectric conversion layer contains a perovskite compound composed of monovalent cations, divalent cations, and halogen anions; the electron transport layer contains a metal oxynitride having electronic conductivity, The metal oxynitride is 1×10 -7 S / cm or more of electrical conductivity, the metal oxynitride is niobium oxynitride; In the niobium oxynitride, the ratio N / O of the amount of N to the amount of O is 0.05 or more and 0.28 or less. Solar cell.
2. The monovalent cation comprises a formamidinium cation. The solar cell according to claim 1 .
3. The halogen anion includes an iodide ion. The solar cell according to claim 1 or 2.
4. The divalent cation includes at least one selected from the group consisting of tin ions and lead ions. The solar cell according to claim 1 .
5. a hole transport layer is provided between the second electrode and the photoelectric conversion layer; The solar cell according to claim 1 .
Citation Information
Patent Citations
High-quality electron transmission layer perovskite solar cell and preparation method thereof
CN107331775A
Photoelectric converter and photovoltaic device using the same
JP2005064493A
Manufacturing method of light-emitting device
JP2016164891A
Perovskite solar battery
JP2017017252A
Solid-state junction photoelectric converter
JP2018157147A
Cited By
Method for manufacturing solar battery and solar battery
JP2025040385A